Pure ICL Implantation: A Novel Ophthalmic Viscosurgical Device-Free Method - Qin Qin; Lianyun Bao; Zifang He; Feifei Chen; Dandan Zhu; Si Zhang; Wenwen Zhang; Yajun Liu; Ruiying Gao; Zhenggao Xie (Journal of Ophthalmology)
Purpose. To assess the clinical efficiency of a novel ophthalmic viscosurgical device-free (OVD-free) method for intraocular collamer lens (EVO-ICL) implantation in myopic eyes. Methods. In this study, 40 patients underwent ICL implantation for both eyes: one eye underwent traditional ICL implantation, and the other eye underwent OVD-free (pure) ICL implantation. Preoperative and postoperative UDVA, BCVA, equivalent spherical degree (SE), IOP, visual quality index, subjective visual quality scale, corneal endothelial cell density (ECD), operation time, and complications were compared between and within the traditional and pure ICL implantation groups. Results. Increased IOP >22 mmHg 2 h after surgery was noted in 8 eyes (20%) in the traditional group, but not in the pure group (0%, P<0.001). Increased IOP relative to baseline was significantly higher at 2 h after surgery for the traditional group compared with the pure group (P<0.001). UDVA, BCVA, and SE were significantly improved in the pure group compared with those in the traditional group 1 day (P<0.001, P=0.003) after implantation, but not 1 week or 3 months after. Modulation transfer function cut-off frequency (MTF cut-off), Strehl ratio (SR), and OV20% were significantly better in the pure group than in the traditional group 1 day after implantation (P=0.013, P=0.009, and P=0.004). No significant difference in ECD changes within or between groups was observed (P>0.05). The operation time for the pure group (2.897 ± 0.346 min) was significantly shorter than that for the traditional group (4.444 ± 0.656 min; P<0.001). No complications were reported for either group during the observation period, except early IOP elevation in the traditional group. Conclusions. The pure ICL implantation method was associated with faster visual acuity recovery, shorter operation time, and more stable intraocular pressure. Pure ICL represents a safe and convenient method for ICL implantation compared with the traditional method, completely eliminating OVD-related complications without causing additional complications.